The role of the mobile museum in promoting National Identity and the Background Kingdom of Saudi Arabia - Nagaiti, Noha Saeed; Qurban, Mrouj Hatem (Journal of Humanities & Social Sciences, 2023)
This study aimed to determine the community’s needs to design a mobile museum that promotes the national identity and background of Saudi Arabia. The study problem revolved around the following question: what is the role of mobile museums in promoting the national identity and background of Saudi Arabia? This study based on a descriptive-analytical approach that used questionnaire. Which included general information for (241) participants and their preferences about mobile museums.  The study concluded significant results; two-thirds of the participants supported the notion of mobile museums, which will aid in achieving Vision 2030 in terms of promoting national identity. The study also found that mobile museums attracted more visitors than permanent museums. Significant recommendations included the activation of mobile museums by the appropriate authorities and the designers’ commitment to improving the quality of life in Saudi cities by delivering innovative and creative notions in the design of museums.
Keywords: interior design; museums; mobile museum; national identity